Quae in ipso coitu observanda: técnica compositiva en un capítulo de la Universa muliebrium morbōrum medicīna de Rodrigo de Castro - González Manjarrés, Miguel Ángel (Ágora: estudos clássicos em debate, 2021)
In this paper, we analyse Rodrigo de Castro's techniques of composition in a chapter taken from De universa muliebrium morb ō rum medic ī na (1.3.5). We seek to understand Castro's use of sources and examine his procedures for assembling his materials. Castro's technique is based on the reelaboration and relocation of data drawn from various sources (particularly the Gynaeci ō rum libri ), with the intent of providing a clear, well-ordered, manageable and useful text. A better knowledge of these compositional strategies will allow us to more justly appreciate the real contribution of this work on gynecology and obstetrics.